Effect of Ratcheting on Tensile Behavior of Zircaloy-2 at Room Temperature - Rajpurohit R.S.; Santhi Srinivas N.C.; Singh S.R.; Singh V. (My University, 2025)
Asymmetric cyclic loading, known as ratcheting fatigue, causes accumulation of cyclic plastic strain and reduces fatigue life of components. This investigation was undertaken to examine the effect of pre-ratcheting on tensile properties of the Zircaloy-2. Stress controlled fatigue tests were performed at room temperature (RT) for 200 cycles with different combinations of the parameters: mean stress (σm), stress amplitude (σa) and stress rate (σ˙). Tensile properties of these samples were evaluated at room temperature. There was marked increase in the yield strength but there was far less effect on the tensile strength. The ductility was reduced due to prior ratcheting. The results have been discussed in terms of work hardening under different combinations of the ratcheting parameters. © 2017, The Indian Institute of Metals - IIM.